إدارة الجودة: دراسة في المفاهيم والدلالات من منظور إسلامي: QUALITY MANAGEMENT: A STUDY OF CONCEPTS AND SEMANTICS FROM ISLAMIC PERSPECTIVE - Elzoubi, Omar Ali; Khan, Issa; bin Mohd Balwi, Mohd Abdul Wahab Fatoni (Online Journal of Islamic Management and Finance (OJIMF), 2021)
There are many quality models around the world, and all of them originated and developed according to the western perspective of management, which seems to be a major challenge facing management in Islamic thought. This is what made the research seeks to address the problem of setting a conception of the Islamic concept of quality management. Therefore, this paper aimed to establish the concept of quality and semantics at the institutional level in line with the Islamic perspective. The paper relied on descriptive and content analysis approaches to access the extrapolation and analysis of the jurisprudential literature in order to build a perception of quality from the Islamic perspective. This paper concluded that there is a clear difference between traditional management and Islamic management, this difference made the adoption of traditional quality models become a great challenge for Islamic institutions. The philosophy of work in Islam goes beyond the goal in achieving customer satisfaction, to strive to obtain the satisfaction of Allah through, His worship and following ihsān in the work. Accordingly, the researchers recommended the necessity of building the Islamic quality model that is consistent with the Islamic model of management.